2021
DOI: 10.21203/rs.3.rs-440491/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The trend of disruption in the functional brain network topology of Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is a progressive disorder associated with cognitive dysfunction that alters the brain’s functional connectivity. Assessing these alterations has become a topic of increasing interest. However, a few studies have examined different stages of AD from a complex network perspective that cover different topological scales. This study analyzed the trend of functional connectivity alterations from a cognitively normal (CN) state through early and late mild cognitive impairment (EMCI and LMCI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Connectivity changes in large-scale networks related to Alzheimer’s disease have been observed with both fMRI and M/EEG (Yu et al ., 2021). For example, Alzheimer’s disease pathology has been associated with changes to functional connectivity of the default-mode network and/or frontoparietal network (Engels et al ., 2015; Klaassens et al ., 2017; Mandal et al ., 2018; Zhao et al ., 2019; Wales and Leung, 2021; Yang et al ., 2021; Fathian et al ., 2022; Moffat et al ., 2022; Zhukovsky et al ., 2023) and networks responding in mismatch paradigms (Başar et al ., 2017; Jovicich et al ., 2019; Nguyen et al ., 2019; Cope et al ., 2022; Gjini et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Connectivity changes in large-scale networks related to Alzheimer’s disease have been observed with both fMRI and M/EEG (Yu et al ., 2021). For example, Alzheimer’s disease pathology has been associated with changes to functional connectivity of the default-mode network and/or frontoparietal network (Engels et al ., 2015; Klaassens et al ., 2017; Mandal et al ., 2018; Zhao et al ., 2019; Wales and Leung, 2021; Yang et al ., 2021; Fathian et al ., 2022; Moffat et al ., 2022; Zhukovsky et al ., 2023) and networks responding in mismatch paradigms (Başar et al ., 2017; Jovicich et al ., 2019; Nguyen et al ., 2019; Cope et al ., 2022; Gjini et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…By acting as a communication conduit between various gray matter regions, white matter plays a key role in several cognitive processes including immediate and delayed memory, processing speed, executive functions, and global cognition 58,59 . Numerous studies have shown that white matter abnormalities are associated with worse cognitive decline in individuals with mild cognitive impairment (MCI) and AD dementia 60–65 . Decreased global efficiency in structural networks is increasingly recognized as a key component of cognitive deficit severity in MCI and AD patients 63–65 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that white matter abnormalities are associated with worse cognitive decline in individuals with mild cognitive impairment (MCI) and AD dementia 60–65 . Decreased global efficiency in structural networks is increasingly recognized as a key component of cognitive deficit severity in MCI and AD patients 63–65 . At the micro‐structural level, reductions in FA and elevations in MD are commonly observed as indicators of compromised white matter in addition to being associated with cognitive decline in individuals with MCI and AD 66,67 .…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, due to their stochastic nature brain signals have often been modeled using their underlying dependence networks. For instance in Bullmore and Sporns ( 2009 ), Henry et al ( 2020 ), and Fathian et al ( 2022 ), the authors use graph theoretical methods on complex brain networks.…”
Section: Modeling Dependence Patterns In Multivariate Time Seriesmentioning
confidence: 99%
“…In the literature, the topology of the brain network (structural and functional) is believed to be organized according to principles that maximize the flow of information and minimize the energy expenditure for maintaining the entire network, such as small world networks (Sporns, 2013 ; Pessoa, 2014 ; Muldoon et al, 2016 ; Henry et al, 2020 ; Fathian et al, 2022 ). This topological structure of the brain network can be altered by various conditions such as attention deficit hyperactivity disorder (ADHD), Alzheimer's and Parkinson's diseases.…”
Section: Introductionmentioning
confidence: 99%